Competitive Dynamics in the Sharing Economy: An Analysis in the Context of Airbnb and Hotels - Li, Hui; Srinivasan, Kannan (Marketing Science, 2019)
This paper studies how the sharing economy fundamentally changes the way the industry accommodates demand fluctuations and how incumbent firms should strategically respond in the context of Airbnb and hotels.